From the Village to the Neighbourhood - Toni García (A+BE: Architecture and the Built Environment)
This thesis examines urban transformation and opportunities for urban upgrading through the rehabilitation and recycling of public housing neighbourhoods built in intermediate cities with a rural base and slow growth.